Glaciological Data Collected by the 39th and 40th Japanese Antarctic Research Expedition during 1998-2000 - Furukawa, Teruo; Yamada, Tomomi; Suzuki, Keisuke; Suzuki, Toshitaka; Matsuoka, Kenichi; Horikawa, Kazuhisa; Murakata, Eishin; Yasugahira, Kazuya; Iizuka, Yoshinori (National Institute of Polar Research, 2002)
P(論文) departmental bulletin paper